Projeto de uma caixa de redução para detecção de defeitos em engrenagens por análise de vibração - ALMEIDA, Rafhael Silva de (2022)
The emergence of new technologies provides more accurate tools to monitor the operation of rotating machines. Maintenance in large companies is of paramount importance, as a full operation of their equipment allows for better performance and productivity. Several maintenance methods have been created over the years by industries in order to reduce costs related to unexpected machine stops. One of the methods developed was vibration analysis, which allows the monitoring and monitoring of machines through mechanical vibration, where each equipment has its signature. The presence of anomalies in this signal can be indicative of failure, which can lead to production losses or unexpected stops. In this work, the development of the design of a gearbox for studies focused on vibration analysis will be demonstrated. In addition, it will be validated through vibration analysis, focusing on defect analysis in a geared pair. Thus, through vibration analysis detect these failure indicators, and also identify where it is inserted, in addition it is possible to notice the presence of other forms of defect such as mechanical clearances, misalignments, defects in bearings.